Study of The Implementation of Merdeka Belajar-Kampus Merdeka Program: The Prevalence of Motives and Perceptions of Competitive Readiness in The Business and The Industrial World - Teguh Sulistyo; Ayu Liskinasih; Maria Purnawati (Universitas Kanjuruhan Malang, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) is a relatively new program, so there are still many obstacles in the process of preparation, implementation, and evaluation. This study aims to see students' motives and perceptions of the implementation of the MBKM program they have carried out in preparation for facing competition in the business / industrial world (DUDI). This research applies quantitative methods with exploratory designs. The respondents in the study were 62 students of the English Literature Study Program at PGRI Kanjuruhan University malang semesters 1, 3, 5, and 7 who were selected using stratification sampling techniques. This study indicates that students get many benefits from MBKM regardless of the obstacles and concerns they face. The MBKM program brings students closer to the business and industrial world because they can directly experience work life. Students have confidence that they can compete in business and industry after they graduate, so they think that MBKM benefits soft skills and hard skills according to their respective passions.